Research on the Development of "Vehicle-Road-Cloud Integration" - Tan, Lingling; Dong, Bo (International Journal of Mechanical and Electrical Engineering, 2024)
"Vehicle-Road-Cloud Integration" is key to solving the industrial development of intelligent connected vehicles and is also an important enabling technology for smart transportation. On July 3, 2024, the Ministry of Industry and Information Technology and four other departments released the list of pilot cities for the application of "Vehicle-Road-Cloud Integration" for intelligent connected vehicles, identifying 20 cities (alliances) as the first batch of pilot cities for "Vehicle-Road-Cloud Integration." The announcement of the pilot application list will accelerate the transition of intelligent driving from small-scale testing to large-scale implementation, further speeding up the widespread application and commercialization of advanced intelligent driving.